Periodontitis and Tooth Loss Have Negative Systemic Impact on Circulating Progenitor Cell Levels: A Clinical Study - Isola, Gaetano (Genes (Basel), 2019)
The aim of the present study was to investigate the association and impact of periodontitis and tooth loss on a subtype of endothelial progenitor cell (EPC) levels (CD133(+)/KDR(+)). Furthermore, the objective was to determine if the periodontal status influenced CD133(+)/KDR(+) levels. In all, 88 patients with periodontitis and 79 healthy controls (HCs) were enrolled in the study. Enrolled patients were examined and characterized by clinical and blood sample analysis. Spearman’s correlation test was applied in order to assess the interdependence between CD133(+)/KDR(+) levels and all periodontal parameters. In order to estimate a statistically significant trend (p-trend) for ordered CD133++/KDR+ quartiles, the Jonckheere–Terpstra test was applied for all variables. Patients in the periodontitis group presented significantly lower CD133(+)/KDR(+) levels (66.4 (45.5–269.6 cells/µL)) compared to the HC group (76.7 (24.3–313.2 cells/µL), p < 0.001). Lower CD133(+)/KDR(+) levels negatively correlated with C-reactive protein (CRP), with the number of teeth, and with all periodontal parameters (p < 0.001). Moreover, there was a proportional increase in CD133+/KDR+ levels with a progressive increase in number of teeth (p-trend < 0.001), while there was a proportional decrease in CD133+/KDR+ levels with a proportional increase in clinical attachment level (CAL, p-trend = 0.003), probing depth (PD, p-trend = 0.007), and bleeding sites (bleeding on probing (BOP), p-trend < 0.001) as an extent measure of periodontitis. This study demonstrated that patients with periodontitis presented significantly lower CD133(+)/KDR(+) levels compared to HCs. Moreover, all patients presented an increase in the CD133(+)/KDR(+) EPC levels with an extended level of periodontitis and tooth loss.